ISLAMIC ENTREPRENEURSHIP BASED ON THE CONCEPT OF HONESTY - Syahrul, Syahruni; Abdullah, M. Wahyuddin (Jurnal Iqtisaduna, 2019)
Islamic entrepreneurship is an aspect of life that grouped into the problem of mu'amalah. This study aims to elaborated entrepreneurship in an Islamic perspective with the concept of honesty which has implications for strengthening Islamic values in entrepreneurial activities  that  can  bring  people  closer  to  Allah swt.  This  study  used  library  research  with descriptive analysis method. All data collected by reviewing various books, literature, notes, including research that has not been or has been published to look for some references relating to Islamic entrepreneurship and the concept of honesty. It is known that the concept of entrepreneurship of the Prophet Muhammad was carried out by means of shiddiq, amanah, tabligh, fathonah according shariah principle as human representation to prospering the earth. The concept of entrepreneurship as solely because of Allah swt.